Overview of Molecular Dynamics Simulation of Natural Gas Hydrate at Nanoscale. (25th June 2021) - Qi, Rongrong; Qin, Xuwen; Bian, Hang; Lu, Cheng; Yu, Lu; Ma, Chao
Abstract : As a dynamic research method for molecular systems, molecular dynamic (MD) simulation can represent physical phenomena that cannot be realized by experimental means and discuss the microscopic reaction mechanism of things from the molecular level. In this paper, the previous research results were reviewed. First, the MD simulation process was briefly described, then, the applicability of different molecular force fields in the natural gas hydrate (NGH) system was discussed, and finally, the application of MD simulation in the formation and decomposition law of NGH was summarized from the perspective of NGH mining. The results show that the selection of water molecular force field has a great influence on the simulation results, and the evaluation of water model applicable to the simulation of NGH under different thermodynamic states is still an open research field that needs to be paid attention to. The effect of surface properties of porous media (such as crystallinity and hydrophilicity) on hydrate needs to be further studied. Compared with thermodynamic inhibitors, kinetic inhibitors (such as amino acids) have more promising research prospects, and further research can be carried out in the screening of efficient kinetic inhibitors in the future.